Metal–nitrogen (Co-g-C3N4) doping of surface-modified single-walled carbon nanohorns for use as an oxygen reduction electrocatalyst. Issue 31 (8th March 2016) - Deng, Li; Zhu, Mingyuan
Abstract : A cobalt-doped graphitic carbon nitride (g-C3 N4 ) polymer was supported on surface-modified single-walled carbon nanohorns (SWCNHs) to produce a new Co-g-C3 N4 catalyst for the oxygen reduction reaction (ORR). Abstract : A cobalt-doped graphitic carbon nitride (g-C3 N4 ) polymer was supported on surface-modified single-walled carbon nanohorns (SWCNHs) to produce a new Co-g-C3 N4 catalyst for the oxygen reduction reaction (ORR). X-ray photoelectron spectroscopy results show that Co–N bonds are formed and that strong electronic coupling occurs between the SWCNHs and Co-g-C3 N4 . The as-fabricated catalysts exhibit reasonable ORR activity, high selectivity, and outstanding electrochemical stability in alkaline media. These results are attributed to the large number of stable Co–N x active sites, high percentage of pyridinic N and rapid mass transport on the "Dahlia flower"-like SWCNHs surface. The fabricated Co-g-C3 N4 /SWCNHs catalyst has potential for use as a non-precious metal cathodic catalyst in fuel cell applications.